2022
DOI: 10.3389/fonc.2022.873037
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA RP11-732M18.3 Promotes Glioma Angiogenesis by Upregulating VEGFA

Abstract: Gliomas are the most aggressive and common type of malignant brain tumor, with limited treatment options and a dismal prognosis. Angiogenesis, a hallmarks of cancer, is one of two critical events in the progression of gliomas. Accumulating evidence has demonstrated that in glioma dysregulated molecules like long noncoding RNAs (lncRNAs), are closely linked to tumorigenesis and prognosis. However, the effects of and mechanisms of action of lncRNAs during tumor angiogenesis are poorly understood. The effect of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Circ-RPL15 up-regulates VEGF-A by competitively binding miR-146b-3p, thereby triggering proliferation and migration potential of glioma (Wang et al 2020a , b ). Except as ceRNA, LncRNA RP11-732M18.3 promotes EP300 into the nucleus to enhance transcription and secretion of VEGF-A, and thus promote angiogenesis in glioma (Kang et al 2022 ). TPT1-AS1 regulates angiogenesis in colon cancer by regulating expression and stability of VEGF-A mRNA through NF90 (Zhang et al 2020a , b , c , d ).…”
Section: Regulation Of Vegf-a Expression In Tumorsmentioning
confidence: 99%
“…Circ-RPL15 up-regulates VEGF-A by competitively binding miR-146b-3p, thereby triggering proliferation and migration potential of glioma (Wang et al 2020a , b ). Except as ceRNA, LncRNA RP11-732M18.3 promotes EP300 into the nucleus to enhance transcription and secretion of VEGF-A, and thus promote angiogenesis in glioma (Kang et al 2022 ). TPT1-AS1 regulates angiogenesis in colon cancer by regulating expression and stability of VEGF-A mRNA through NF90 (Zhang et al 2020a , b , c , d ).…”
Section: Regulation Of Vegf-a Expression In Tumorsmentioning
confidence: 99%
“…Bioinformatics analysis found that lncRNA expression patterns in clinical glioma specimens correlated with histological differentiation and malignancy grade, which may have remarkable clinical impacts for glioma sub-classification, diagnosis, and prognostication ( 20 ). Other studies found that RP11-732M18.3 was highly overexpressed in glioma cells, which not only promote glioma angiogenesis by accelerating the transcription and secretion of VEGFA but also facilitate glioma growth through accelerating p21 degradation ( 21 , 22 ). More recently, a risk model of constructed from eleven inflammation-related lncRNAs was reported as a potential prognostic biomarker for patients with lower-grade gliomas ( 23 ).…”
Section: Introductionmentioning
confidence: 98%